Advancement and New Understanding in Brain Injury - Idris, Zamzuri (IntechOpen, 2021)
This book covers the latest developments in the understanding and treatment of traumatic brain injury. Various world experts authored the chapters that comprise a wealth of updated information on intracranial pressure; monitoring and diagnostic methods; neuroinflammatory responses in traumatic brain injury; cerebral palsy and Covid-19-related brain disorder; pathogenesis and prevention of fetal, neonatal, infant, and child brain injury; hyperbaric oxygenation treatment; the engineering and modeling of head injury; systematic review on early-tracheostomy; intracranial aneurysm in tuberous sclerosis complex; and the neurobehavioral and cognitive aspects of brain injury. With these complex topics, every clinician, scientist, and researcher will find this book invaluable in understanding the latest improvements and advances in the diagnosis and treatment of traumatic brain injury.